Noble tool based micromilling for nanometric surface finish - Ali, Mohammad Yeakub (Ministry of Higher Education, Malaysia, 2011)
This research introduced micro electro discharge (ED) milling as a potential technique to fabricate miniaturized components. It investigated the influence of three micro ED milling process parameters, which were feed rate, capacitance and voltage. The response variables were average surface roughness (Ra), maximum peak-to-valley roughness height (Ry), tool wear ratio (TWR) and material removal rate (MRR). Tungsten was used as the tool-electrode while beryllium-copper (Be-Cu) alloy was the workpiece. Statistical models of these output responses were developed using three-level full factorial design of experiment. The developed models were used for multiple response optimization by desirability function approach to obtain minimum Ra, Ry, TWR and maximum MRR. Maximum desirability of 88% was obtained. The optimized values were experimentally verified. The optimized values of Ra, Ry, TWR and MRR were 0.04 μm, 0.34 μm, 0.044 and 0.08 mg/min respectively, which were obtained at feed rate of 4.79 μm/s, capacitance of 0.10 nF and voltage of 80 volts. Using these process parameters, a micro swiss-roll combustor mold cavity of Be-Cu alloy was fabricated. This mold cavity can be used for mass replication by micro hot embossing or microinjection molding, which is economical compared to conventional fabrication techniques. The nano level surface finish shows the technical competency of micro ED milling over other fabrication techniques such as laser micromachining, micromilling, etc.